Acute transplant renal artery thrombosis due to distal renal artery stenosis: A case report and review of the literature - Mohammad Kazem Fallahzadeh; Rajini Kanth Yatavelli1; Ajay Kumar; Neeraj Singh (Society of Diabetic Nephropathy Prevention, 2014)
Background: Acute renal artery thrombosis is a devastating complication of renal transplantation that can result in graft loss if not detected early. Surgical and technical errors are the major cause of renal artery thrombosis. In this article, for the first time, we are reporting a case of acute renal artery thrombosis that developed early post-transplantation due to distal renal artery stenosis. Case Presentation: A 71-year-old woman presented with nausea, vomiting and decreased urine output 7 days after a deceased donor kidney transplant. Doppler ultrasound showed absent renal and venous flow in the transplanted kidney. Transplant renal artery angiogram showed renal artery thrombosis. Catheterization and thrombectomy were done in the occluded renal artery. After thrombectomy, renal angiogram showed distal renal artery stenosis which was dilated by stenting. Post-stenting angiogram showed good blood flow in the entire renal arterial system. However, the patient's kidney function did not improve within next 24 hours and the patient eventually lost the kidney. Kidney biopsy showed widespread kidney infarction with no evidence of rejection. Conclusions: Our case shows that renal artery thrombosis can develop due to distal renal artery stenosis and if not detected early could result in graft loss.